The Impact of Digital Transformation and ESG Disclosure on Tax Avoidance: Does Audit Committee Matter? - Agus Fuadi; Sindik Widati; Amelia Anggareni (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study examines the impact of digital transformation and Environmental, Social, and Governance (ESG) disclosure on corporate tax avoidance, with the audit committee serving as a moderating variable. The increasing emphasis on corporate digitalization, sustainability reporting, and governance has created the need to understand how these factors jointly influence firms' tax behavior. This study employs a quantitative explanatory research design using panel data collected from non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2025 period. Secondary data are obtained from annual reports, sustainability reports, and corporate governance reports and analyzed using panel data regression with moderation analysis. The illustrative findings indicate that digital transformation significantly reduces corporate tax avoidance by improving transparency, information quality, and internal control systems. ESG disclosure is also found to negatively influence tax avoidance, suggesting that firms with stronger sustainability commitments are less likely to engage in aggressive tax planning. Furthermore, the audit committee strengthens the negative relationships between digital transformation, ESG disclosure, and tax avoidance by enhancing monitoring effectiveness and corporate governance quality. These findings contribute to the integration of digital transformation, sustainability reporting, and governance into a comprehensive framework for explaining corporate tax behavior. The study provides practical implications for managers, investors, and regulators in promoting responsible taxation through digitalization, ESG implementation, and effective audit committee oversight.